Fungibility and the Impact of Development Assistance: Evidence from Vietnam's Health Sector - Wagstaff, Adam (2012)
The apparent fungibility of aid is a challenge to the evaluation of donor-funded development projects, requiring a comparison of the observed outcomes with the outcomes that would have occurred if the project had not gone ahead. Where projects are targeted on specific geographic areas, counterfactual outcomes in each can differ from observed outcomes because the amount of government spending (gross of aid) differs, the productivity of government spending differs, or both. This paper estimates the benefits of two concurrent World Bank health projects in Vietnam targeted on specific provinces. Estimates are derived from a model linking outcomes (under-five mortality) to government spending before and after the project and in project and nonproject provinces, and are presented for different assumptions regarding fungibility of funds (zero and full fungibility) and the impacts of the project on the productivity of government spending (the project modifies productivity in both sectors equally and in neither sector). The estimated mortality reductions are highly insensitive to the assumed degree of fungibility, but highly sensitive to the assumed productivity effects (the estimates range from 1 to 25%). The wide range reflects the uncertainty due to the lack of a genuine control group of provinces.